The benefits of auctioneer competition: Merging auctions and adding auctioneers - Alexander Heczko; Thomas Kittsteiner; Marion Ott (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
In a lab experiment, we analyze the benefits of increasing competition on auction platforms hosting multiple auctioneers of a homogeneous good. We find that increasing competition by merging separated individual auctions increases market efficiency and also buyers' payoffs, while there is no evidence of an increase in the auctioneers' expected revenues. Furthermore, competing auctioneers decrease reserve prices significantly when the number of competitors increases. Then, auctioneers' revenues decrease whereas buyers' payoffs and efficiency are enhanced. Different to previous findings for the monopolistic seller case, competing auctioneers do not increase reserve prices significantly when the number of buyers increases. For our theoretical model, we provide closed-form equilibrium reserve-price functions of competing auctioneers.
Keywords: D44; D47; D82; 330; Competing auctions; merging markets; parallel auctions; reserve price; experiment